1990
DOI: 10.1002/j.2161-0045.1990.tb00387.x
|View full text |Cite
|
Sign up to set email alerts
|

The Separate and Combined Effects of SIGI or DISCOVER and a Career Planning Course on Undecided University Students

Abstract: Research to consider the effectiveness of computer-assisted guidance system (CACG) and credit career planning courses was conducted during the 1988 spring semester at Pennsylvania State University and the University of Virginia. The research inethodology included use of a four-group pretest-posttest design at each university. Group treatment conditions using undecided university students were the following: (a) CACG use by students enrolled in a career planning course, (b) students enrolled only in a career pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
11
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
5
11
0
Order By: Relevance
“…Thus, we can infer that the involvement of a counselor in the career exploration process becomes exceedingly important to attain the desired "human" qualities of attractiveness and trustworthiness in social influence. The results of these contrasts support earlier findings that the optimal use of CACG systems occurs when they are employed as components in the overarching counseling process with competent counselors (Garis & Niles, 1990; Kapes, Borman, & Frazier, 1989;Sampson & Stripling, 1979).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, we can infer that the involvement of a counselor in the career exploration process becomes exceedingly important to attain the desired "human" qualities of attractiveness and trustworthiness in social influence. The results of these contrasts support earlier findings that the optimal use of CACG systems occurs when they are employed as components in the overarching counseling process with competent counselors (Garis & Niles, 1990; Kapes, Borman, & Frazier, 1989;Sampson & Stripling, 1979).…”
Section: Discussionsupporting
confidence: 81%
“…Although questions or fears have been raised periodically over the past 20 years about computers replacing counselors, evidence increasingly accumulates that such feelings or concerns are largely unwarranted (Harris-Bowlsbey, 1983, 1985. A comprehensive review of research studies showed that most institutions use computer-assisted career guidance (CACG) systems as a component within a broader career counseling context (Sampson, Shahnasarian, & Reardon, 1987), and that the desired outcomes of career guidance using CACG systems are most likely to occur when they are used to augment the career counseling process (Garis & Niles, 1990; Kapes, Borman, & Frazier, 1989;Marin, 1984;Rozman & Kahl, 1984;Sampson & Stripling, 1979).…”
mentioning
confidence: 99%
“…The proliferation of computer-assisted career guidance or information systems within educational institutions, governmental agencies, and private organizations has been well documented (e.g., Sampson, Shahnasarian, & Reardon, 1987). This proliferation of systems has led to an increase in research studies investigating their effectiveness (e.g., Garis & Niles, 1990;Sampson, Shahnasarian, & Reardon, 1988). In general, it has been found that computer use results in the acquisition of self and occupational information and in the facilitation of career decision making (Cairo, 1983).…”
mentioning
confidence: 99%
“…In addition, Cooper (1987) crossvalidated the SCD with the My Vocational Situation (MVS) and found the SCD to be an effective index of vocational identity, as well as a measure of other vocational constructs, such as lack of information or training, or environmental or personal barriers. In a study of the concurrent validity of the SCD, a correlation of r = .51 {N = 79) was found between the SCD and MVS indicating some overlap in underlying constructs (Garis and Niles, 1990).…”
Section: Discovermentioning
confidence: 99%